PERAN DESA ADAT DALAM PENERTIBAN PENDUDUK PENDATANG DI KOTA DENPASAR - A. A. Ayu Dewi Larantika (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
The phenomenon of migrants is not foreign to the island of Bali and Denpasar city. Denpasar city as a metropolis with many amenities offered according to the function and its strategic role as the center of government, economy and trade, the activity center of education and health services, as well a center of tourism activities that contribute to the development of Bali's economy, the reason migrants come storming Denpasar city. The rapid flow of migrants coming into the city of Denpasar cause various social problems crate slums, pollution, economic competition, crime and so on. This paper aims to present the various policies adopted by the government of Denpasar to curb settlers, one of them involving indigenous villages. It is therefore interesting to observe how the role of indigenous villages in the demolition of migrants in the city of Denpasar. From observation and interviews as well as studying the existing documentation, it can be said that the role of indigenous villages in the discipline of migrants is very important, because the territory of the island of Bali in general and in particular Denpasar divisible in indigenous villages. The traditional village with customary rules of direct contact and bind communities and this can be one of the strategies in the discipline of migrants in the city of Denpasar.